Implementing static bandwidth allocation in EPON testbed - Radzi N.A.M.; Din N.M.; Sadon S.K.; Al-Mansoori M.H. (2023)
In upstream Ethernet passive optical network (EPON) transmission, timeslot needs to be allocated as the needs to share a single fiber from a splitter to the optical line terminal (OLT) can cause a collision. The allocation is usually being studied using simulations, but it does not take into account the physical parameters. This paper shows a study on static bandwidth allocation (SBA) in upstream EPON using a peripheral interface controller (PIC) testbed. To the best of our knowledge, this is the first time SBA is being implemented in testbed. The result proves that the PIC testbed can be used to test the allocation method of EPON. 2012 IEEE.